Pooling of central taxes for devolution. - Gulati, I.S. (1995)
"The pooling of central taxes for devolution to the states, as recommended by the Tenth Commision under its `alternative scheme', is very narrowly conceived. The Commission ignores possible alternatives such as transfer of the entire field of domestic trade taxation to the states"
Keywords: Finance, Public - India; Taxation - India